2020
DOI: 10.1039/d0ta00682c
|View full text |Cite
|
Sign up to set email alerts
|

Mass-producible polyhedral macrotube carbon arrays with multi-hole cross-section profiles: superb 3D tertiary porous electrode materials for supercapacitors and capacitive deionization cells

Abstract: Supercapacitors and capacitive deionization (CDI) cells used for energy storage and water desalination, respectively, are related devices which are based on intensive adsorption of ions to highly porous electrodes. Engineering...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…The higher CDI performance of 750°C material can be contributed to its high specific surface area and suitable pore structure. The electrosorption performance of 3D porous carbon by carbonization process of lotus stems at 400, 500, and 600°C was compared by Ma, Wu, et al (Ma, Wu, et al, 2020). The sample carbonized at 500°C outperforms than the other two samples.…”
Section: Materials Perspectivementioning
confidence: 99%
“…The higher CDI performance of 750°C material can be contributed to its high specific surface area and suitable pore structure. The electrosorption performance of 3D porous carbon by carbonization process of lotus stems at 400, 500, and 600°C was compared by Ma, Wu, et al (Ma, Wu, et al, 2020). The sample carbonized at 500°C outperforms than the other two samples.…”
Section: Materials Perspectivementioning
confidence: 99%
“…Hierarchically porous carbon [91][92][93][94] 3D carbon aerogel [96,97] Low tap density High surface area More exposed surface area for charge storage…”
Section: Dmentioning
confidence: 99%
“…For example, Zhou et al [91] successfully prepared a 3D hierarchically interconnected porous carbon material through the pyrolysis of Rhus typhina fruit followed by post-activation in which the pores inside the Rhus typhina fruit precursor were well maintained without significant collapse during preparation, resulting in widespread porous distribution in the as-acquired carbon material. Ma et al [92] also easily mass-produced polyhedral macrotube carbon arrays with a hierarchical porous structure using lotus stems and reported that benefitting from a unique tertiary porous structure with hierarchical porosity and large SSA (> 2500 m 2 g -1 ), the sample exhibited a high specific capacitance of > 370 F g -1 at 1 A g -1 in 6 M KOH and achieved an energy density of 9.3 Wh kg −1 in a symmetric SC device. The direct carbonization of biomass precursors without pretreatment is another method to obtain 3D structures with abundant pores.…”
Section: Three-dimensional Porous Structuresmentioning
confidence: 99%
“…[35,36] Energy storage mainly occurs in smaller micropores, and a large number of micropores and trace mesopores are connected to each other. [37] This is the necessary property of SCs with excellent performance. It is speculated that LRKC8-5 has better electro-chemical performance.…”
Section: Materials Characterizationsmentioning
confidence: 99%